Orbital rhabdomyosarcoma in an adult - Lavaju, P; Das, H; Malla, P; Tiwari, A; Sinha, A; Upadhyaya, P (Nepalese Journal of Ophthalmology, 2010)
Introduction: Rhabdomyosarcoma is the most common primary orbital malignant tumor in children. Orbital lesions represent about 10 % of all the cases of rhabdomyosarcoma. Rhabdomyosarcoma is a rare cause of proptosis in adults. Objective: To report a case of primary orbital rhabdomyosarcoma in a 45-year-old female. Design: Interventional case report. The main outcome measures are a rare cause of proptosis in an adult, discussion on treatment options and prognosis of rhabdomyosarcoma. Result: The patient underwent total orbital exenteration and was referred for radiotherapy and chemotherapy. Conclusion: Rhabdomyosarcoma is a rare cause of proptosis in adults. It should be suspected in a case of rapidly-progressive proptosis in adults. DOI: 10.3126/nepjoph.v2i1.3707 Nep J Oph 2010;2(1) 64-67